Physical and cognitive demands of work in building construction. Issue 3 (9th October 2019) - Rodriguez, Franciscsa S.; Spilski, Jan; Hekele, Felix; Beese, Nils Ove; Lachmann, Thomas
Abstract : Purpose: Investigating demands within an occupational context has always been an essential endeavor to guarantee worker well-being and performance efficiency. In blue-collar occupations, the physical demands of manual labor have always been the major focus, but recent technological changes may come with higher demands on the intellectual capacities of workers. For this reason, the purpose of this paper is to assess physical and cognitive demands that construction workers face. Design/methodology/approach: The authors conducted a quantitative study using standardized research instruments. Construction workers of three German construction companies were asked to volunteer to participate in interviews ( n =35) and a survey ( n =30) that assessed the extent of physical demands and a variety of cognitive demands experienced by construction workers. Findings: The results suggest that construction work is demanding in physical terms as well as in perceptual, psychomotor, social and cognitive terms. Using and updating specialized knowledge, giving advice and providing consultation, friendliness, assertiveness and reliability are important demands among construction workers. Research limitations/implications: Construction workers face an undervalued level of demands in their everyday work environment. As high demands can affect well-being and mental health, construction companies would greatly benefit from investing efforts into evaluating the multi-component demands profile of their workers and the impact on their health, in particular through the strongly increasing cognitive demands due to the ongoing digitization of the sector. Originality/value: The study identified essential demands in construction work that are relevant for the workers' productivity and well-being.